PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP PRESTASI KERJA DENGAN OCB SEBAGAI VARIABEL PEMEDIASI - Puspitasari, Ni Luh Made Ria (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2015)
Insurance agent is an essential  element in order to  maintain the existence of the insurance companies in  the business  competition.  This  study  aimed  to  investigate  the  eff ect  of   j ob  satisfaction  and  organizational  commitment on insur ance agent tur nover intention.  This study was conducted at PT. PRUDENTIAL INDONESIA - Bali. Simple  r andom  sampling  was  used  because  of  homogeneous  population  characterist ic.  160  questionnai res were  distributed,  and  only  155  questionnaires  were  returned  by  the  respondents.  Structural  Equation  Modeling (SEM)  using AMOS  16.0  was  used  to  test  the  research  hypothesis.  The  resul ts  of  the  study  support   all  the hypothesis  and  indicate  that  job  satisfaction has  significant  posi tive  effect  on  organizational  commi tment  so  it is  advisable  for the company to  continue improvement  of  the job satisfaction of insurance  agent s in  order  to enhance  organizational  commitment.  In  contrast,  job  satisfaction  and  organizational  commitment  consistently show a negat ive and  significant  effect on  turnover intention
Keywords: job sat isfaction, organizational commitment, turnover intention, insurance agent